2012
DOI: 10.1371/journal.pone.0046008
|View full text |Cite
|
Sign up to set email alerts
|

Gradual Loss of ACTH Due to a Novel Mutation in LHX4: Comprehensive Mutation Screening in Japanese Patients with Congenital Hypopituitarism

Abstract: Mutations in transcription factors genes, which are well regulated spatially and temporally in the pituitary gland, result in congenital hypopituitarism (CH) in humans. The prevalence of CH attributable to transcription factor mutations appears to be rare and varies among populations.This study aimed to define the prevalence of CH in terms of nine CH-associated genes among Japanese patients. We enrolled 91 Japanese CH patients for DNA sequencing of POU1F1, PROP1, HESX1, LHX3, LHX4, SOX2, SOX3, OTX2, and GLI2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 24 publications
2
17
0
2
Order By: Relevance
“…In all the patients, mutations in POU1F1, PROP1, HESX1, LHX3, LHX4, OTX2, SOX2, SOX3, and GLI2 have been excluded by PCR-based sequencing (4). Gene copy number aberrations in POU1F1, PROP1, HESX1, LHX3, and LHX4 were also excluded by multiplex ligation-dependent probe amplification (MLPA) analyses (4). Approval for this study was obtained from the Institutional Review Board of Keio University School of Medicine.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all the patients, mutations in POU1F1, PROP1, HESX1, LHX3, LHX4, OTX2, SOX2, SOX3, and GLI2 have been excluded by PCR-based sequencing (4). Gene copy number aberrations in POU1F1, PROP1, HESX1, LHX3, and LHX4 were also excluded by multiplex ligation-dependent probe amplification (MLPA) analyses (4). Approval for this study was obtained from the Institutional Review Board of Keio University School of Medicine.…”
Section: Subjectsmentioning
confidence: 99%
“…Echocardiogram revealed a patent ductus arteriosus, which was surgically corrected at 1 month of age. At the age of 1 year, he was diagnosed with central hypothyroidism with a low fT 4 Table 4, see section on supplementary data given at the end of this article). The brain MRI exhibited anterior pituitary hypoplasia, visible but thin stalk, and EPP (Fig.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Previous studies have shown that GH and PRL cells may be inter-changeable, as progenitors may differentiate into GH, which is later transformed into PRL (Di Iorgi et al, 2012a;Tsai et al, 2012). Recent studies in fish and birds have supported the theory that PRL and GH follow an independent differentiation (Jagtap et al, 2012;Takagi et al, 2012). Other studies, however, did not detect the expression of PRL in the embryonic pituitary (Garcia Martin et al, 2010;Sukhija et al, 2012).…”
mentioning
confidence: 99%
“…Agenesis or hypoplasia of the ICA is a rare vascular anomaly seen in about 0.01% of the population [10]. Twelve cases of agenesis of the ICA accompanied by CPHD have been reported so far [8,11,12,13,14,15,16,17,18,19,20,21].…”
Section: Discussionmentioning
confidence: 99%